Conocimientos y actitudes con relación al aborto: Una encuesta a estudiantes de educación superior de la provincia de San Martín - Perú - 1995 - López Llanos, Alma Soledad (1996)
This research is descriptive, prospective data collection, obtained from students of the National University of San Martin, Technological North Eastern Jungle and State Pedagogical Institute of Higher Institute Tarapoto. Information obtained in situ based on surveys used for execution. A sample of 575 students who represent 25% of all students enrolled in the aforementioned centers being selected last cycles of the various academic programs were noted. The ee survey conducted in November 15 to December 15, 1995. Students received sexual education by 50% more in the home, school and university. There were talks deficiency on birth control at home while in school and higher center was optimal. Loe most used contraceptive methods were the condom, rhythm and pill. Over 50% of students received lectures about abortion in college and university. The frequency of abortions in men who underwent a partner to practice abortion is 64.77% and 35.23% in women who did so by choice. Less than 50% of students agreed with the legalization of abortion aborto.La approval of majority was caused in selective cases. The independent variable that reached significance was the high opinion on the legalization of abortion.